Severity of Childhood Trauma is Predictive of Cocaine Relapse Outcomes in Women but not Men - Hyman, Scott M. (2007)
We prospectively examined the gender-specific effects of childhood trauma on cocaine relapse outcomes in an inpatient sample of treatment engaged cocaine dependent adults. Cocaine dependent men (n = 70) and women (n = 54) participating in inpatient treatment for cocaine dependence were assessed on severity of childhood trauma and followed for 90 days after discharge from treatment. Greater severity of childhood emotional abuse was associated with an increased risk of relapse in women. Severity of emotional abuse, sexual abuse, and overall childhood trauma was associated with the number of days cocaine was used during follow-up in women, as was the association of severity of physical abuse and overall childhood trauma with the average amount of cocaine used per occasion. No associations between childhood trauma and cocaine relapse outcomes were found in men. These findings demonstrate that childhood trauma increases the likelihood of cocaine relapse and drug use escalation after initial relapse in women but not in men. Comprehensive assessments of childhood trauma and specialized treatments that address trauma-related pathophysiology could be of benefit in improving cocaine treatment outcomes in women.